Instability of traveling waves for a generalized diffusion model in population problems - Changchun Liu (Electronic Journal of Qualitative Theory of Differential Equations, 2004)
In this paper, we study the instability of the traveling waves of a generalized diffusion model in population problems. We prove that some traveling wave solutions are nonlinear unstable under $H^2$ perturbations. These traveling wave solutions converge to a constant as $x→∞$.